2000
DOI: 10.1021/jo000219w
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of 1,5-Disubstituted Pyrrolidin-2-ones

Abstract: 1,5-Disubstituted pyrrolidin-2-ones 18a-g, 19a-h, and 20a-f were synthesized in good to excellent yields via the nucleophilic substitution of 5-(benzotriazol-1-yl)-1-substituted-pyrrolidin-2-ones 9 with allylsilanes, organozinc reagents, and phosphorus compounds. Compounds 9 and 5-(benzotriazol-2-yl)-1-substituted-pyrrolidin-2-one isomers 10 are readily prepared in total 70-84% yields from 2, 5-dimethoxy-2,5-dihydrofuran (7), primary amines 8, and benzotriazole; 9 and 10 react identically with nucleophiles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“…The reaction of 2,5-dimethoxy-2,5-dihydrofuran 63, benzotriazole, and primary amines in refluxing AcOH gave 5-benzotriazolyl-1-substituted-pyrrolidin-2-ones 64 in good yields, with strong preference for the benzotriazol-1-yl isomer (Scheme 20) [76]. Substitution of the benzotriazolyl moiety in 64 with nucleophiles gave 5-substituted 2-pyrrolidinones 65-67.…”
Section: Pyrrolidinonesmentioning
confidence: 99%
See 2 more Smart Citations
“…The reaction of 2,5-dimethoxy-2,5-dihydrofuran 63, benzotriazole, and primary amines in refluxing AcOH gave 5-benzotriazolyl-1-substituted-pyrrolidin-2-ones 64 in good yields, with strong preference for the benzotriazol-1-yl isomer (Scheme 20) [76]. Substitution of the benzotriazolyl moiety in 64 with nucleophiles gave 5-substituted 2-pyrrolidinones 65-67.…”
Section: Pyrrolidinonesmentioning
confidence: 99%
“…Treatment of intermediates 64 with 4 equiv. of trimethylallyl-or trimethyl(2-methylallyl)silane in the presence of a Lewis acid furnished 1-substituted-5-allylpyrrolidinones 65 (Scheme 21) [76].…”
Section: Pyrrolidinonesmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Cotinine 2 is a metabolite of nico-tine and is found in tobacco, 2 it can cross the blood brain barrier and has interesting medicinal properties (Fig. 6 Katritzky et al 7 and Sun et al 6 have also reported on the importance of this calss of compound. 3 γ-Lactams with quaternary stereogenic centres at C5, such as dysibetaine 3, displays neuroexcitotoxine activity.…”
Section: Introductionmentioning
confidence: 99%
“…Katritzky et al reported the synthesis of pyrrolyl-benzotriazoles by the Mannich condensation of o-phthalaldehyde and 2,5-dimethoxy-2,5-dihydrofuran with primary amines, 12) but this method was not effective for pyrroles, and the desired products were produced only in less than 10% yields. As a new approach, the oxidative C-H bond functionalization strategies of pyrroles [13][14][15][16][17][18][19][20][21][22] might be expected to be an attractive methodology for enabling rapid access to these molecules.…”
mentioning
confidence: 99%